2019
DOI: 10.32861/jssr.52.408.417
|View full text |Cite
|
Sign up to set email alerts
|

Economic Transformation in Bangladesh and the Income Velocity of Broad Money: An Econometric Analysis

Abstract: This study has undertaken an econometric analysis of economic transformation and income velocity of broad money. To find out the relevant determinants of income velocity of money this paper used time series data on year basis. This paper focus to discover the key determinants of the velocity of money in Bangladesh using the Augmented Dicky Fuller (ADF) unit root test to inspect the stationary, Engle-Granger residual-based cointegration approach to demonstrate the co-integrating association among variables. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…However, in short-term estimations, inflation has a significant negative effect on the income velocity of money. These results are different from those of previous studies by Al-Tamimi [31], Luo, et al [19], Roy, et al [20], and Khanom [28], which found that the relationship between velocity of money and inflation is positive. Depending on how it affects money balances and income growth more generally, inflation's influence on the velocity of money can be either positive or negative.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in short-term estimations, inflation has a significant negative effect on the income velocity of money. These results are different from those of previous studies by Al-Tamimi [31], Luo, et al [19], Roy, et al [20], and Khanom [28], which found that the relationship between velocity of money and inflation is positive. Depending on how it affects money balances and income growth more generally, inflation's influence on the velocity of money can be either positive or negative.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, economic growth partially has long-and short-run effects on the income velocity of money in Indonesia. In the study by Khanom [28], economic growth was found to have a negative impact on the income velocity of money in Model 1 and a positive effect in Model 2. Income velocity shows how quickly or frequently people use their income as a means of payment for economic transactions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is proven by the hypothesis assumed by previous researchers. The results of this study obtained the same results as the research conducted by Susmiati et al (2021), Khanom (2019), Firmansyah (2016), and Jumhur et al (2018. An increase in the money supply will have a major impact on increasing inflation in the country.…”
Section: Discussionsupporting
confidence: 82%
“…The study of Khanom (2019) examined the determinants of the velocity of money in Bangladesh during the period 1972-2015.…”
Section: The Determinants and Effects Of The Velocity Of Moneymentioning
confidence: 99%